Game of thrones. The complete second season [videorecording (DVD)] - Benioff, David; Weiss, D. B. (Warner Home Video, 2013)
Kings from across the continent of Westeros vie for the Iron Throne. As winter approaches, the cruel young Joffrey sits upon the Throne in King's Landing, counseled by his conniving mother Cersei and his uncle Tyrion, who has been appointed the new Hand of the King. But the Lannister hold on power is under assault on many fronts, with two Baratheons donning crowns, and Robb Stark fighting as the King in the North.